Application properties of a cyclophosphamide-core polyamidoamine dendritic montmorillonite in natural rubber composites. Issue 5 (June 2020) - Cheng, Liu; Jincheng, Wang; Wen, Zhao; Shiqiang, Song
This work focused on investigation of application properties of organoclay-modified natural rubber (NR) composites. This organoclay, flame-retardant (FR) dendrimer-modified organic montmorillonite (G-OMMT), was composed of dendrimer and montmorillonite. Different generations of G-OMMT were prepared. G3.0-OMMT was selected and FR composites were fabricated. Their tensile properties, thermal stability, flame-retardance, and other properties were compared. The tensile strength and elongation at break of NR/G3.0-OMMT-15 were 18.8 MPa and 586%, respectively, which were about 12.6% and 23.6% higher than that of pure NR, 16.7 MPa and 474%. In addition, when 10 phr of G3.0-OMMT was added, the wearing loss volume was 0.231 cm 3, which was 42.4% lower compared with that of pure NR, 0.401 cm 3 . The NR composites also possessed better thermal stability. When the amount of this organoclay was 10 phr, T 5% and T 10% were 306.4°C and 349.5°C, respectively. They were 102.3°C and 29.2°C higher than that of pure NR. Moreover, the burning rate was decreased from 30.15 mm min −1 for pure NR to 19.48 mm min −1 for NR/G3.0-OMMT-20, and the limited oxygen index value was increased from about 18% for pure NR to about 28% for NR/G3.0-OMMT-20. Scanning electron microscopy analysis demonstrated that the layered silicates dispersed uniformly in these composites and possessed a good compatibility with the polymeric matrix.